Associations of perceived neighborhood factors and Alzheimer’s disease polygenic score with cognition: Evidence from the Health and Retirement Study - Erin B. Ware; Peiyao Zhu; Grace Noppert; Mingzhou Fu; Mikayla Benbow; Lindsay C. Kobayashi; Lindsay H. Ryan; Kelly M. Bakulski (PLoS ONE, 2025)
Background We examined the relationships between neighborhood characteristics, cumulative genetic risk for Alzheimer’s disease (polygenic scores for Alzheimer’s disease), and cognitive function using data from the Health and Retirement Study (2008–2020, age > 50). Methods Baseline perceived neighborhood characteristics were combined into a subjective neighborhood disadvantage index. Cognitive function was assessed at baseline and measured biennially over a 10-year follow-up period. Analyses were stratified by genetic ancestry. Cox proportional hazard models analyzed associations between neighborhood characteristics, Alzheimer’s disease polygenic scores, and their interactions on cognitive impairment. Results In the European ancestries sample, a one standard deviation higher score on the subjective neighborhood disadvantage index was associated with a higher hazard of any cognitive impairment (HR:1.09; CI:1.03–1.15), cognitive impairment without dementia (HR:1.08; CI:1.03–1.14), and dementia (HR:1.13; CI:1.03–1.24). Similarly, a one standard deviation increase in Alzheimer’s disease polygenic score was associated with a higher risk of cognitive impairment (HR:1.10; CI:1.05–1.16) and cognitive impairment without dementia (HR:1.10; CI:1.05–1.16) but not dementia (HR:1.05; CI:0.96–1.16). No significant interactions were found. Evidence in African ancestries were directionally similar but imprecise and inconclusive due to limited precision and cross-ancestry polygenic score transferability. Subjective neighborhood disadvantage index and Alzheimer’s disease polygenic score were independently associated with incident cognitive impairment. Conclusions Preventing dementia by addressing modifiable risk factors is essential.